2015
DOI: 10.1371/journal.pone.0136078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhibiting Dipeptidyl Peptidase-4 (DPP4) in Cows with Subclinical Ketosis

Abstract: The inhibition of dipeptidyl peptidase-4 (DPP4) via specific inhibitors is known to result in improved glucose tolerance and insulin sensitivity and decreased accumulation of hepatic fat in type II diabetic human patients. The metabolic situation of dairy cows can easily be compared to the status of human diabetes and non-alcoholic fatty liver. For both, insulin sensitivity is reduced, while hepatic fat accumulation increases, characterized by high levels of non-esterified fatty acids (NEFA) and ketone bodies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Thus, early lactating cows seem to be in an immunologically more dysregulated T cell balance compared to later stages of lactation. This finding is in general agreement with recent findings in transition cows (Schulz et al 2015, Tienken et al 2015) but contrasts another experiment where time and treatment (body condition score, monensin, essential oils) around calving influenced the CD4+/CD8+ ratio in an interactive manner (Drong et al 2016). A successive increase in dietary energy concentration resulted in a significant decrease of the CD4+/CD8+ ratio from 2.5 to 2.1 in non-gravid and non-lactating cows (Dänicke et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, early lactating cows seem to be in an immunologically more dysregulated T cell balance compared to later stages of lactation. This finding is in general agreement with recent findings in transition cows (Schulz et al 2015, Tienken et al 2015) but contrasts another experiment where time and treatment (body condition score, monensin, essential oils) around calving influenced the CD4+/CD8+ ratio in an interactive manner (Drong et al 2016). A successive increase in dietary energy concentration resulted in a significant decrease of the CD4+/CD8+ ratio from 2.5 to 2.1 in non-gravid and non-lactating cows (Dänicke et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…reported similar results in high-fat-fed animals, including reduction in plasma non-esterified fatty acids, after 14 weeks of treatment with evo-gliptin [ 114 ]. Moreover, a study conducted in cows showed how the use of DPP4i was related to reduced non-esterified fatty acids and triglycerides levels [ 115 ]. In addition, sitagliptin reduced intestinal cholesterol absorption in obese insulin-resistant mice, suggesting another potential mechanism translating into improved cholesterol metabolism [ 116 ].…”
Section: Novel Anti-diabetic Drugsmentioning
confidence: 99%
“…Hormone Analyses. For trial 1, RIA was used for determining the insulin concentrations (IM3210, Insulin IRMA KIT, Immunotech, Beckman Coulter, Brea, CA) as described previously (Schulz et al, 2015). The intra-assay coefficient of variation (CV) was 7.6% and the interassay CV was 10.7%; the limit of detection (LOD) was 3.95 µU/mL.…”
Section: Analysesmentioning
confidence: 99%